2009
DOI: 10.1063/1.3263144
|View full text |Cite
|
Sign up to set email alerts
|

Increasing organic vertical carrier mobility for the application of high speed bilayered organic photodetector

Abstract: External quantum efficiency versus charge carriers mobility in polythiophene/methanofullerene based planar photodetectorsThe direct influence of the vertical carrier mobility on the frequency response of bilayered organic photodiodes ͑PDs͒ is investigated for the first time. With fullerene as the acceptor material, changing vertical hole mobility from 2.3ϫ 10 −5 to 2.8ϫ 10 −4 cm 2 / V s increases PD bandwidth from 10 to 80 MHz under a 4 V operation. The influence of deposition rate on vertical hole mobility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 8 publications
1
28
0
Order By: Relevance
“…[ 184 ] We draw the attention of the reader to the diverse range of proposed strategies to increase the speed of resp onse. [ 103,183,[185][186][187] …”
Section: Reviewmentioning
confidence: 98%
“…[ 184 ] We draw the attention of the reader to the diverse range of proposed strategies to increase the speed of resp onse. [ 103,183,[185][186][187] …”
Section: Reviewmentioning
confidence: 98%
“…Recently, the study of OPDs made of pentacene and C 60 has shown that the utilization of organics with high carrier mobility can increase the bandwidth of the OPDs. 10 As we known, crystalline rubrene holds the distinction of being the organic semiconductor with the highest carrier mobility, which reaches 40 cm 2 V À1 s À1 for holes. 11 The hole mobility of amorphous rubrene can also reach the range of 7-9 Â 10 À3 cm 2 V À1 s À1 at room temperature.…”
mentioning
confidence: 95%
“…The G is ≈626 at the wavelength of 532 nm obtained by EQE spectrum (equivalent to 6.26 × 10 4 % of EQE), τ c in this work is 74 µs, V is 1 V, and d is 360 nm, obtaining a calculated µ of 1.1 × 10 −2 cm 2 V −1 s −1 . Although the µ across the device is much smaller than that of the perovskite materials because of the lower µ of PCBM (≈10 −3 cm 2 V −1 s −1 ), it still has a large improvement compared with organic photodetectors (≈10 −4 to ≈10 −3 cm 2 V −1 s −1 ), which is due to the reduced carrier transport path in organic materials and rapid transmission in perovskite. Figure S5 (Supporting Information) shows the normalized response as a function of pulse frequency.…”
Section: Resultsmentioning
confidence: 99%